The antidepressant tianeptine reverts synaptic AMPA receptor defects caused by deficiency of CDKL5. (30th March 2018) - Tramarin, Marco; Rusconi, Laura; Pizzamiglio, Lara; Barbiero, Isabella; Peroni, Diana; Scaramuzza, Linda; Guilliams, Tim; Cavalla, David; Antonucci, Flavia; Kilstrup-Nielsen, Charlotte
Abstract: Mutations in the X-linked cyclin-dependent kinase-like 5 ( CDKL5 ) gene cause a complex neurological disorder, characterized by infantile seizures, impairment of cognitive and motor skills and autistic features. Loss of Cdkl5 in mice affects dendritic spine maturation and dynamics but the underlying molecular mechanisms are still far from fully understood. Here we show that Cdkl5 deficiency in primary hippocampal neurons leads to deranged expression of the alpha-amino-3-hydroxy-5-methyl-4-iso-xazole propionic acid receptors (AMPA-R). In particular, a dramatic reduction of expression of the GluA2 subunit occurs concomitantly with its hyper-phosphorylation on Serine 880 and increased ubiquitination. Consequently, Cdkl5 silencing skews the composition of membrane-inserted AMPA-Rs towards the GluA2-lacking calcium-permeable form. Such derangement is likely to contribute, at least in part, to the altered synaptic functions and cognitive impairment linked to loss of Cdkl5. Importantly, we find that tianeptine, a cognitive enhancer and antidepressant drug, known to recruit and stabilise AMPA-Rs at the synaptic sites, can normalise the expression of membrane inserted AMPA-Rs as well as the number of PSD-95 clusters, suggesting its therapeutic potential for patients with mutations in CDKL5.